Über Sepedophilus cavicola (Scriba, 1870) und S. crypticola (Rey, 1881) (Coleoptera: Staphylinidae, Tachyporinae). - Schülke, Michael (Beiträge zur Entomologie = Contributions to Entomology, 1998)
Sepedophilus crypticola (Rey, 1881) wird mit Sepedophilus cavicola (Scriba, 1870) synonymisiert. Stichwörter Coleoptera, Staphylinidae, Tachyporinae, Sepedophilus, Europe, New synonym. Nomenklatorische Handlungen crypticola Rey, 1881 (Conurus), Lectotype; syn. n. of Sepedophilus cavicola (Scriba, 1870) cavicola (Scriba, 1870) (Sepedophilus), Lectotype described as Conosoma cavicola